Impact of enhanced optical techniques at time of transurethral resection of bladder tumour, with or without single immediate intravesical chemotherapy, on recurrence rate of non-muscle-invasive bladder cancer: a systematic review and network meta-analysis of randomized trials - Sari Motlagh, Reza; Mori, Keiichiro; Laukhtina, Ekaterina; Aydh, Abdulmajeed; Katayama, Satoshi; Grossmann, Nico C; Mostafai, Hadi; Pradere, Benjamin; Quhal, Fahad; Schuettfort, Victor M; Roshandel, Mohammad Reza; Karakiewicz, Pierre I; et al. (BJU international, 2021)
OBJECTIVE: To assess whether single immediate intravesical chemotherapy (SIIC) adds value to bladder tumour management in combination with novel optical techniques: enhanced transurethral resection of bladder tumour (TURBT). METHODS: A systematic search was performed using the PubMed and Web of Science databases in September 2020 according to the Preferred Reporting Items for Systematic Review and Meta-analysis (PRISMA) extension statement for network meta-analyses. Studies that compared recurrence rates among intervention groups (TURBT with photodynamic diagnosis [PDD] ± SIIC, narrow-band imaging [NBI] ± SIIC, or white-light cystoscopy [WLC] + SIIC) and a control group (TURBT with WLC alone) were included. We used the Bayesian approach in the network meta-analysis. RESULTS: Twenty-two studies (n = 4519) met our eligibility criteria. Out of six different interventions including three different optical techniques, compared to WLC alone, blue-light cystoscopy (BLC) plus SIIC (odds ratio [OR] 0.349, 95% credible interval [CrI] 0.196-0.601) and BLC alone (OR 0.668, 95% CrI 0.459-0.931) were associated with a significantly lower likelihood of 12-month recurrence rate. In the sensitivity analysis, out of eight different interventions compared to WLC alone, PDD by 5-aminolevulinic acid plus SIIC (OR 0.327, 95% CrI 0.159-0.646) and by hexaminolevulinic acid plus SIIC (OR 0.376, 95% CrI 0.172-0.783) were both associated with a significantly lower likelihood of 12-month recurrence rate. NBI with and without SIIC was not associated with a significantly lower likelihood of 12-month recurrence rate (OR 0.385, 95% CrI 0.105-1.29 and OR 0.653, 95% CrI 0.343-1.15). CONCLUSION: Blue-light cystoscopy during TURBT with concomitant SIIC seems to yield superior recurrence outcomes in patients with non-muscle-invasive bladder cancer. The use of PDD was able to reduce the 12-month recurrence rate; moreover, concomitant SIIC increased this risk benefit by a 32% additional reduction in odds ratio. Although using PDD could reduce the recurrence rate, SIIC remains necessary. Moreover, ranking analysis showed that both PDD and NBI, plus SIIC, were better than these techniques alone.
Keywords: kombinovaná terapie; narrow band imaging; aplikace intravezikální; Combined Modality Therapy; Administration, Intravesical; lokální recidiva nádoru; nádory močového měchýře; #BladderCancer; Urethra; randomizované kontrolované studie jako téma; non-muscle-invasive urothelial carcinoma; blue-light cystoscopy; photodynamic diagnosis; #blcsm; Neoplasm Recurrence, Local; lidé; Humans; Randomized Controlled Trials as Topic; uretra; hexaminolevulinic acid; Cystectomy; cystektomie; Urinary Bladder Neoplasms; #uroonc; single immediate intravesical chemotherapy